UNDERSTANDING THE ROLE OF SELF-MANAGEMENT AND PEER SOCIAL INTERACTION IN ENHANCING ACADEMIC ACHIEVEMENT OF ISLAMIC EDUCATION MANAGEMENT STUDENTS AT STAI AL HIDAYAH BOGOR - Rahman, Rahman; Sarifudin, Sarifudin; M. Hidayat Ginanjar; Lily Nova Amalia; Jully Triansyah (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2024)
This study was conducted in the context of character development among students at SDIT Al-Mughni Jakarta through the Pesantren Ramadhan (Sanram) and Basic Student Leadership Training (LDKS) programs. This study aimed to analyse Sanram and LDKS's influence on students' character formation. The research method was a quantitative survey, collecting data through questionnaires distributed to sixth-grade students participating in both programs. The results showed that Sanram had a more dominant influence, with a regression coefficient of 0.445, compared to LDKS, which had a regression coefficient of 0.372. Nonetheless, combining both programs provided a more optimal contribution to students' character development. The conclusion of this study highlights the importance of integrating religious programs and leadership training into the character education curriculum in schools. These findings underscore the need for a more holistic approach to designing educational strategies for effective character development. Suggestions for future research include a deeper evaluation of the effectiveness of integrating these two programs and consideration of individual internal factors and the influence of family and social environments.